Operation optimization of electrical-heating integrated energy system based on concentrating solar power plant hybridized with combined heat and power plant. (20th March 2021) - Li, Xin; Gui, De; Zhao, Zhangfei; Li, Xinyu; Wu, Xian; Hua, Yawen; Guo, Panfeng; Zhong, Hao
Abstract: The integration of power and heating systems is a promising option to optimize unit operation and improve power system flexibility for reducing renewable energy sources curtailment. This study aims to excavate the potentiality of a concentrating solar power plant hybridized with a gas-fired combined heat and power plant to alleviate the effects of the uncertainty and variability of renewable energy sources. Firstly, in order to further utilize the scheduling ability of the concentrating solar power plant with a thermal energy storage (TES) system and improve the operational flexibility of the combined heat and power plant, a combined plant is proposed in this paper. Specifically, a concentrating solar power plant and a gas-fired combined heat and power unit are assembled together based on the temperature parameters of energy flow during operation. Secondly, taking the remaining state of charge (SOC) of TES in operating day into account, a three-stage multi-time scale stochastic unit commitment-economic dispatch model is formulated to optimize unit operation and reduce operating cost. Finally, in order to verify the operational flexibility and economic benefits of the proposed combined plant with multi-time scale stochastic unit commitment-economic dispatch model, several different energy supply modes are compared in the simulation. Results show that the proposed scheme has better economic benefits and development potential in the electrical-heating integrated energy system. Highlights: A hybrid CSP-CHP plant is proposed based on the scheduling ability of CSP plant with TES and the operation mode of CHP plant. The detailed process of the energy flow in a hybrid CSP-CHP plant is described. A three-stage multi-time scale stochastic unit commitment-economic dispatch model considering the remaining SOC of TES at the end of operating day is formulated. The operational flexibility and economic benefits of the proposed mode are analyzed through comparing several energy supply modes.